Lower serum insulin-like growth factor 2 level in patients with bipolar disorder is associated with the severity of manic symptoms during manic episodes - Ye, Shi-Yi; Zhao, Ying; Liu, Zhao-Bo; Luo, Cui-Pin; Xiong, Jian-Wen; Zhan, Jin-Qiong; Li, Yi-Heng; Wei, Bo; Chen, Chun-Nuan; Yang, Yuan-Jian (Frontiers in Psychiatry, 2024)
Objective: Accumulating evidence has indicated that neurodevelopmental defects may underlie the pathophysiology of bipolar disorder (BD). Insulin-like growth factors (IGFs) are a family of neurotrophic factors that are essential for the survival and development of neurons. The present study aims to investigate whether IGF-2 signaling is implicated in the pathophysiological processes of BD.Method: 50 healthy controls and 78 patients with BD, including 23 patients who diagnosed acute depressive episode and 55 patients who diagnosed acute manic episode, were recruited in this study.The 17-item Hamilton Depression Rating Scale (HAMD-17) and the Young Mania Rating Scale (YMRS) were used to assess the severity of the depressive and manic symptoms, respectively. The serum IGF-2 level was determined by an enzyme-linked immunosorbent assay (ELISA). The Kolmogorov-Smirnov and Mann-Whitney U tests were used for between-group comparisons and spearman analysis was used to analyze correlations.Results: Patients with BD had lower serum IGF-2 levels (66.08 ± 21.22 ng/ml) when compared to healthy controls (88.72 ± 31.55 ng/ml). BD patients were divided into manic episode and depressive episode subgroups. We found that serum IGF-2 levels were reduced in both the mania and depression subgroups (mania: 67.19 ± 21.52 ng/ml, depression: 63.43 ± 20.67 ng/ml; P < 0.001), while no significant difference was observed between two groups (P > 0.05). Spearman correlation analyses revealed that the levels of serum IGF-2 were negatively correlated with the YMRS scores in BD patients (r = -0.522, P < 0.001). Furthermore, IGF-2 was found to be an independent contributor to the severity of symptoms in patients with manic episodes (B = -0.610, t = -5.299, P < 0.001).Conclusion: Lower serum IGF-2 levels were found in BD patients and correlated with the severity of the manic symptoms in these patients during manic episodes. These results suggest that reduced IGF-2 levels might be involved in the pathophysiology of BD, and serum IGF-2 could be a peripheral biomarker for the evaluation of the severity of manic symptoms in BD patients.